Diversidade de Palaemonideos, Alpheideos e Merguiideos (Caridea: Alpheoidea, Palemonoidea) na Amazônia Oriental. - PAIXÃO, Erik Daniel Santos da (2024)
The present work aims to provide updated data on Carcinofauna in the northern region of Brazil, specifically on decapod crustaceans, together with a dichotomous key and photographs of the specimens, to aid in their respective identification. The importance of this study lies in the production of a faunal list focused on the bragantina region, which will contribute to biodiversity assessments within the vast northern region (BARROS & PIMENTEL 2001). Artisanal traps were used to capture shrimp in estuaries and freshwater specimens during a period of 1 year (between May 2022 and April 2023). During this interval, a total of 15 collections were carried out. Subsequently, the collected specimens were relocated to the Carcinology laboratory at UFPA/IECOS. The animals were identified using dichotomous keys and photographed to aid in their identification. The results obtained indicate the presence of 4 new occurrences of shrimp in the bragantina region. Among these new occurrences, 3 are from marine water and 1 from fresh water. These belong to 3 different families: Alpheidae (genus: Alpheus), Palaemonidae (genus: Macrobrachium) and Merguiidae (genus: Merguia). Furthermore, it was possible to observe that two of these new reported occurrences belong to a complex of species and for this reason may present morphological characteristics distinct from individuals of the same family/genus (Alpheus lobidens and Alpheus floridanus). This work directly contributes to a better knowledge of the local Carcinofauna, since studies on the decapod fauna of the bragantina peninsula are minimally known, in particular the group of crustaceans.